(untitled) (International Journal of Engineering and Computer Science, 2017)
Disease Prediction has always been a matter of research due to increasing number of health risks. Modern Medicine System produce huge amount of data which needs to be organized. Medical Data Mining plays a vital role in generating efficient results when it comes to prediction based analytics. Data Mining turns data into patterns which are useful for analyzing the diseases. This research paper focuses on role of K-Means Algorithm in disease prediction